UPAYA MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII G MELALUI BANTUAN SCAFFOLDING di SMPN 1 GEGER - Diah Ayu Marsela Wati, Alpina; Krisdiana, Ika; Suparmono, Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this study is to describe the implementation model of Problem Based Learning (PBL) assisted by Scaffolding techniques. This study is also to determine students' mathematical communication skills after the implementation of Problem Based Learning (PBL) assisted by Scaffolding techniques. This research was conducted in class VIIG of SMPN 1 Geger at 2024/2025 academic year. The Classroom Action Research (CAR) design was carried out in 2 cycles, in which the data collection instruments were in the form of test questions and observation sheets. Based on the findings, cycle 1 did not meet the success criteria, so the research was continued to cycle 2. In cycle 2, the success criteria had been achieved, so the Classroom Action Research (CAR) was said to be successful. Furthermore, the communication skills of students are also increased. Some points that must be considered in implementating this learning procedures are firstly, teachers must pay attention to the allocation of time provided for each step of learning in accordance with the Learning Implementation Plan. Secondly, the teacher must optimize his role as a facilitator in Problem Based Learning (PBL) through various scaffolding techniques. Some of the techniques given here can be adapted to other learning models and materials. The teacher needs to be more selective in choosing the right technique for optimalizing learning.